2002
DOI: 10.1088/0953-2048/15/12/316
|View full text |Cite
|
Sign up to set email alerts
|

Magnetization of multiply connected superconductors with and without  -junctions loops

Abstract: The magnetic behavior of Multiply Connected Superconductors (MCS) can be described analyzing the simplest loop structures containing Josephson junctions: conventional loops with all conventional Josephson junctions and π-loops with an odd subset of πjunctions. These last are unconventional Josephson junctions in which the coupling has the reversed sign and appears in the ceramic materials as consequence of d-pairing. Among MCS the magnetic behavior of large β two-dimensional Josephson Junction Arrays (JJA) is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
3
0

Year Published

2003
2003
2008
2008

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…We note that magnetization of paramagnetic state is zero at a threshold field η * ≃ 0.29. The linear decrease of mean is similar to that observed for (large β) single loops [18]. For the parameters of Fig.…”
supporting
confidence: 83%
See 2 more Smart Citations
“…We note that magnetization of paramagnetic state is zero at a threshold field η * ≃ 0.29. The linear decrease of mean is similar to that observed for (large β) single loops [18]. For the parameters of Fig.…”
supporting
confidence: 83%
“…In general a loop containing p Josephson junctions will have different magnetization states when a magnetic field is applied. If the junctions are identical the loop current I n is a solution of the following equation [18]:…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The usage of π−JJs as passive π−shifters in RSFQ circuits was recently suggested in reference [18], and realized in [19]. Moreover, recent studies (both theoretical and experimental) of JJ arrays with π−JJs have shown some novel features arising out of the interplay between 0− and π−JJs [20,21,22,23,24,25,26,27,28,29,30]. For instance, when a 2π kink is introduced in a hypothetical parallel array with alternating 0− and π−JJs [31], it will break up into two separate π−kinks.…”
Section: Introductionmentioning
confidence: 99%